The Policy and Practice on the Conservation of Hui (Muslim) Folk Sports Culture in China: A Historical Review. Issue 12 (13th August 2017) - He, Pingxiang; Hong, Fan; Zheng, Guohua
Abstract: Since the founding of the People's Republic of China (PRC), governments at all levels, central and local, have made and implemented a series of policies and laws to conserve Hui (Muslim) sports culture, support and promote Hui sports, as well as protect and guarantee their sports rights. However, at the first stage of the PRC (1949–1979), the Chinese government utilized the conservation and development of Hui sports culture to enhance national cohesion and establish a united front, thus making Hui sports a means of realizing political objectives. In the post-1980s, Hui folk sports culture has been restored and conservation policies have been regularized and legalized in the context of building a socialist harmonious society. However, the legalization and standardization process is incomplete and requires further study and action.